Clinical management of women at high risk of breast cancer. Issue 1 (February 2015) - Wuttke, Melanie; Phillips, Kelly-Anne
<x xml:space="preserve">Abstract</x> Purpose of review This article reviews the evidence that underpins breast cancer screening and prevention strategies for women at high risk of the disease, with a particular focus on evidence published in the last 18 months. The review is timely because the US National Comprehensive Cancer Network, the UK National Institute for Health and Care Excellence and the American Society of Clinical Oncology have recently updated relevant guidelines that inform practice. Recent findings In the recently published literature, there have been several important findings. A meta-analysis of randomized trials of selective oestrogen receptor modulators (SERMs), along with the first results from the International Breast Cancer Intervention Study II trial, further support the use of SERMs and aromatase inhibitors in the primary prevention of breast cancer. A large observational study has provided evidence that the SERM tamoxifen may be efficacious for breast cancer prevention in women who carry mutations in the breast cancer predisposition genes, BRCA1 and BRCA2. Several observational studies have suggested that contralateral risk-reducing mastectomy, following a diagnosis of breast cancer, may reduce mortality. Summary Evidence regarding the optimal management of women at high risk of breast cancer continues to evolve and needs to be rapidly implemented into clinical practice.